Brassinolide and BZR1 are up-regulated in a parthenocarpic mutant of prickly pear - Ramakrishnan, Rameshkumar; Zurgil, Udi; Tarkowská, Danuše; Novák, Ondřej; Strnad, Miroslav; Tel-Zur, Noemi; Sitrit, Yaron (Plant cell reports, 2025)
Parthenocarpic fruit development in prickly pear involves up-regulation of the transcription factor BZR1 and increased levels of brassinolide in developing ovules. We explored the complex process of parthenocarpic fruit development in prickly pear Opuntia ficus-indica (Cactaceae) by comparing the fruits of the parthenocarpic Beer Sheva1 (BS1) mutant and revertant non-parthenocarpic fruits. The mutant plants produce flowers with enlarged ovules that develop into degenerated seed-like stony structures. Pollen tubes fail to penetrate the ovule, resulting in the formation of lignified and hard seed coat brown in colour. Some new stems on BS1 plants bear normal revertant flowers containing small and viable fertilized ovules. BS1 thus provides a unique model for elucidating the regulatory mechanisms underlying parthenocarpy in prickly pear. Our working hypothesis was that parthenocarpy is induced by elevated levels of brassinolide in the ovules of BS1. By comparing transcriptomes, we identified 7717 differentially expressed genes between BS1 and the revertant among them brassinosteroid-related genes. Quantification of the brassinosteroids confirmed higher brassinolide levels and up-regulation of the brassinosteroid positive regulator BRASSINAZOLE RESISTANT1 (BZR1) in BS1 ovules compared to revertant ovules displaying normal seed development. Thereby, implicating the involvement of brassinolide in ovule development, fruit phenology, and parthenocarpy. The early flowering and fruit ripening observed in BS1 support our hypothesis that brassinolide promotes parthenocarpic fruit development and ripening.
Keywords: upregulace; BZR1; Up-Regulation; steroidy heterocyklické; Steroids, Heterocyclic; mutace; Brassinolide; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; brassinosteroidy; Cacti; rostlinné proteiny; Prickly pear; vajíčko rostlin; Opuntia; Opuntia ficus-indica; Flowers; Brassinosteroids; ovoce; Plant Proteins; Ovule; květy; Fruit; Mutation; Parthenocarpy